Tareas extra clases en el proceso de aprendizaje en estudiantes de octavo año de educación ganeral básica de la unidad educativa Kléber Franco Cruz de Machala 2013-2014. - Castillo Manzanillas, Nelly Georgina (2014)
opening that gave us the authorities of the educational unit Kléber Franco Cruz, who allowed to apply this thesis research has generated expectations in education must be recognized. The conceptual theoretical content points out issues that defines the importance of the implementation of the extra class tasks to the learning process of learners, issues that directly affect academic performance.